(untitled) (Orinoquia, 2016)
In the fish sector identified in the municipality of Pasto, department of Nariño, there is an inadequate culture of cooperation on the part of small and medium enterprises that participate in the productive chain. Therefore, an associative strategy is proposed to improve the competitiveness of the sector, increasing the production and commercialization of trout, for which it was necessary to carry out a quantitative study of a descriptive - comprehensive type with empirical analytical approach, as a result of this study, it is analyzed that the organizations that participate in this productive chain, have not yet efficiently using the opportunities that the external environment offers them, being necessary to establish alternatives that allow them to face the threats, improve the strengths and mitigate the weaknesses in the contexts in which it operates (environmental, commercial, business and productive); allowing the development of adequate processes and procedures, lowering production costs and other actions that lead to the realization of strategic alliances between the University, Company and State, promoting an export culture with high quality standards. It is also necessary to improve the factors that influence the predisposition to associativity, allowing the appropriation of knowledge with access to new technologies, generating actions that allow improving trust for the fulfillment of commitments and associative agreements, sharing and accessing information of interest. It is concluded that most fish farmers would be willing to associate, in order to access innovation processes with high technology, achieving better production and marketing results, one of the ways to achieve this is through the implementation of a business network as an organizational associative strategy.